Prevalence of resistance to deltamethrin in Rhyzopertha dominica (F.) in eastern Australia. (September 2018) - Daglish, Gregory J.; Nayak, Manoj K.
Abstract: The pyrethroid, deltamethrin, is currently used as a grain protectant to protect stored grain from insect pests in several countries including Australia. We examined the variation in response to wheat treated with deltamethrin among 15 field populations of the lesser grain borer, Rhyzopertha dominica (F.) collected from Queensland and New South Wales in eastern Australia during 2008 and 2009, to establish whether resistance has developed in this species. Based on the results of treated wheat bioassays, using a discriminating dose of 0.5 mg kg −1, we found that 14 of the 15 field populations were resistant to deltamethrin. The distance between the two most geographically separated field populations was 450 km, and both of these populations contained resistant insects. Deltamethrin applied at 1 mg kg −1 alone or with the synergist piperonyl butoxide at 8 mg kg −1 failed to control resistant R. dominica . On the basis of our findings, we conclude that populations with deltamethrin resistant individuals are common in the eastern part of Australia, and control failures are expected when such populations are present in treated grain. Highlights: We investigated resistance to deltamethrin in Rhyzopertha dominica. Resistance was present in 14 of 15 field samples collected from eastern Australia. Control failures are expected when such populations are present in treated grain.